Free Tissue Transfer for Complex Reconstruction of the Lower Extremity: Experience of a Young Microsurgeon - Wink, Jason D.; Nelson, Jonas A.; Fischer, John P.; Cleveland, Emily C.; Kovach, Stephen J., III (Journal of Reconstructive Microsurgery, 2014)
To examine the limb salvage experience of a young microsurgeon to determine risk factors for complications and demonstrate lessons learned through cases in practice. We performed a retrospective review of lower extremity (LE) reconstruction between 2007 and 2012 performed by the senior author. This analysis focused on medical comorbidities, mechanisms, indications, and perioperative complications. A total of 61 free tissue transfers were performed with a 95% LE salvage rate. The most common donor site was the anterolateral thigh (ALT) (n = 39). Infection (n = 25) and trauma (n = 25) were the most common indications for intervention. A total of 18 complications were reported, with 8 defined as major complications. Total flap loss occurred in three patients. Through increased utilization of the ALT and adherence to lessons learned over time, improvements in outcomes can occur, giving patients the best possible chance at limb salvage.
Keywords: lower extremity reconstruction; young microsurgeon; flap loss